Performance Evaluation of a Micro Off-Grid Solar Energy Generator for Islandic Agricultural Farm Operations Using HOMER - Querikiol, Edward M.; Taboada, Evelyn B. (Journal of Renewable Energy, 2018)
A study was conducted to evaluate the performance of a 1.5 kW micro off-grid solar power generator in a 2-hectare area of a 23-hectare agricultural farm located in Camotes Island, Cebu, Philippines (10°39.4′ N, 124°20.9′ E). The area requires at least 3000 liters of water every day to irrigate its plantation of passion fruit and dragon fruit; however, there is no water source within the immediate vicinity that can support such requirement. A 1/2 horsepower water pump was installed to provide the required irrigation. A 1.5 kW solar photovoltaic (PV) system consisting of 6 units of 250-watts solar PV panel with corresponding 6 units of 200 ampere-hour deep cycle batteries managed by a 3-kW industrial grade inverter provided the power for the water pump and supplied for the electricity demand of the farm. The actual energy usage of the farm was measured from the built-in monitoring of the charge controller and the installed system was analyzed to determine its efficiency in meeting the actual load demand. The HOMER optimization tool was used to determine the optimal configuration for the micro off-grid system based on the actual load demand. Simulation results showed that the optimum configuration that could supply the actual load is a 2.63 kW all-PV system with 8 kWh batteries. Sensitivity analysis was done to consider (1) possible increase in electrical load when the current plantation expands either in progression or outright to its full-scale size of 23 hectares and (2) variations in fuel cost. This study can be considered a good model in assessing renewable energy needs of farms in the country, which can be operationalized for agricultural purposes.